Is coffee consumption associated with a lower risk of hyperuricaemia or gout? A systematic review and meta-analysis. Issue 7 (8th July 2016) - Zhang, Yi; Yang, Tuo; Zeng, Chao; Wei, Jie; Li, Hui; Xiong, Yi-lin; Yang, Ye; Ding, Xiang; Lei, Guanghua
Abstract : Objectives: To examine the associations of coffee consumption with the serum uric acid (SUA) level, hyperuricaemia (HU) and gout. Design: Systematic review and meta-analysis. Data sources and study eligibility criteria: A comprehensive literature search up to April 2015, using PubMed and EMBASE databases, was conducted to identify the observational researches that examined the associations of coffee consumption with the SUA level, HU and gout. The standard mean difference (SMD), OR, relative risk (RR) and their corresponding 95% CIs for the highest and the lowest categories of coffee intake were determined. Results: A total of 11 observational studies (6 cross-sectional, 3 cohort and 2 case–control studies) were included in this systematic review and meta-analysis. The combined SMD suggested that there was no significant difference between the highest and the lowest coffee intake categories in terms of the SUA level (SMD=−0.09, 95% CI −0.23 to 0.05; p=0.21). Meanwhile, the overall multivariable adjusted OR for HU showed no significant difference between the highest and the lowest coffee intake categories (OR=0.84, 95% CI 0.65 to 1.09; p=0.20). However, the overall multivariable adjusted RR for gout showed a significant inverse association between coffee consumption and the incidence of gout (RR=0.43, 95% CI 0.31 to 0.59, p<0.001). Conclusions: Current evidences are insufficient to validate the association between coffee consumption and a lower risk of HU. Owing to the limited number of studies, the available data show that coffee consumption may be associated with a lower risk of incident gout. Further well-designed prospective researches and randomised controlled trials are therefore needed to elaborate on these issues.